2007
DOI: 10.1099/vir.0.83198-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GB virus C NS5A protein from genotypes 1, 2, 3 and 5 and a 30 aa NS5A fragment inhibit human immunodeficiency virus type 1 replication in a CD4+ T-lymphocyte cell line

Abstract: GB virus type C (GBV-C) is a common human flavivirus that has been associated with prolonged survival in HIV-positive individuals in several, though not all, epidemiological studies. There are five distinct GBV-C genotypes that are geographically localized, and it has been speculated that GBV-C genotypic differences may explain variable outcomes observed in different clinical studies. Expression of an 85 aa fragment of the GBV-C NS5A phosphoprotein (genotype 2) in a CD4+ T cell line (Jurkat) resulted in inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 30 publications
3
36
0
1
Order By: Relevance
“…Análisis más detallados, han demostrado que la región de la proteína correspondiente a los residuos aminoacídicos del 152 a 236 de la proteína son suficientes para inhibir la replicación del VIH. Adicionalmente, se reportó inhibición cuando se expresó la región con los aminoácidos entre 152-181, región en la que se encuentran cuatro sitios de fosforilación, los cuales serían importantes para la actividad inmunomoduladora, lo que sugiere la existencia de mecanismos adicionales que median la inhibición del VIH 50,51 . Estos resultados sugieren que todos los genotipos del GBV-C son capaces de inhibir la replicación del VIH, y que el posible mecanismo se relaciona con la modulación en la producción de la quimioquina SDF-1, quimioquina con potencial para competir por el co-receptor CXCR4, para lo cual se ha propuesto que es capaz de afectar pasos post-entrada, similar a lo reportado para MIP1-α 52 .…”
Section: Proteína Ns5aunclassified
“…Análisis más detallados, han demostrado que la región de la proteína correspondiente a los residuos aminoacídicos del 152 a 236 de la proteína son suficientes para inhibir la replicación del VIH. Adicionalmente, se reportó inhibición cuando se expresó la región con los aminoácidos entre 152-181, región en la que se encuentran cuatro sitios de fosforilación, los cuales serían importantes para la actividad inmunomoduladora, lo que sugiere la existencia de mecanismos adicionales que median la inhibición del VIH 50,51 . Estos resultados sugieren que todos los genotipos del GBV-C son capaces de inhibir la replicación del VIH, y que el posible mecanismo se relaciona con la modulación en la producción de la quimioquina SDF-1, quimioquina con potencial para competir por el co-receptor CXCR4, para lo cual se ha propuesto que es capaz de afectar pasos post-entrada, similar a lo reportado para MIP1-α 52 .…”
Section: Proteína Ns5aunclassified
“…The protein(s) of GBV-C that lead to HIV inhibition are not defined. Xiang's studies showed that the GBV-C NS5A could inhibit HIV-1 replication [18][19][20]. The effect of GBV-C E2 protein remains to be resolved in HIV-1 co-infection.…”
Section: Introductionmentioning
confidence: 95%
“…GBV-C infection of PBMCs and CD4+ T cells increases secretion of CCR5 ligand chemokines and decreases CCR5 expression by 50% compared with mock-infected PBMCs [30], [31]. Two GBV-C proteins, NS5A [32][35] and the envelope glycoprotein E2 [36][40], inhibit HIV replication in CD4+ Jurkat cells by either decreasing HIV receptor expression (NS5A) or blocking HIV attachment and entry (E2). NS5A expressed in CD4+ Jurkat T cells inhibits HIV replication by decreasing expression of CD4 [35] and CXCR4 [32][34].…”
Section: Introductionmentioning
confidence: 99%
“…Two GBV-C proteins, NS5A [32][35] and the envelope glycoprotein E2 [36][40], inhibit HIV replication in CD4+ Jurkat cells by either decreasing HIV receptor expression (NS5A) or blocking HIV attachment and entry (E2). NS5A expressed in CD4+ Jurkat T cells inhibits HIV replication by decreasing expression of CD4 [35] and CXCR4 [32][34]. This effect is mediated in part by enhanced secretion of the CXCR4 ligand chemokine SDF-1 [33], [34].…”
Section: Introductionmentioning
confidence: 99%